Cybersecurity dan Tata Kelola Intelijen - ikhssani, agung; Mudra, Cakra; Prasidya, Fragmadio Gana (UI Scholars Hub, 2024)
The utilization of information and communication technology crossing national borders opens opportunities for state and non-state actors to engage in various detrimental activities. Information theft, attacks on banking systems, military networks, and national infrastructure pose threats that must be addressed. Cyberspace, with its boundaryless, abstract, and timeless nature, becomes a field for transnational criminal activities. In this context, cybersecurity is not only the responsibility of the government but also requires cross-sector cooperation. Proactive policy development, robust cybersecurity infrastructure, and public-private collaboration are key to protecting critical systems and maintaining national stability. Intelligence governance also plays a crucial role in addressing these threats. The ability to gather, analyze, and integrate information from various sources, both open and closed, enables a quick and effective response to cyber threats. Indonesia faces challenges such as legal limitations and international cooperation in responding to cross-border cybercrimes. Increased collaboration with other countries, as well as regulatory strengthening, is a crucial step in overcoming these obstacles. This article review discusses cybersecurity and intelligence governance in Indonesia.